THE JOURNEY OF LEARNING ENGLISH AND ITS PROFOUND BENEFITS - Jasmina Ismatova Muxammadali qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article explores the journey and benefits of learning English, highlighting its global importance as a lingua franca. It breaks down the learning process into initial, intermediate, and advanced stages, offering strategies for overcoming challenges at each level. The benefits of English proficiency are vast, including enhanced educational opportunities, career advancement, travel ease, personal growth, cognitive improvements, and access to information. Societal advantages include economic growth, social integration, and global collaboration. Despite common barriers like lack of resources and psychological hurdles, technology has made learning English more accessible. The article concludes that learning English is a valuable investment, offering significant returns in knowledge, skills, and opportunities.